A ética do silêncio no delinear da sétima proposição do Ractatus Logico-Philosophicus - Garcia, Caio César da Silva (2018)
In this research we intend to present the course of the first philosophy of Wittgenstein starting from proposition 7, turning the steps of the author in the propositions that are intercalated to produce the ethical sense of the theory of silence, developing in the first chapter a discussion that deals with language, its form of figuration and of the author's proposal to identify which errors that conditioned to the language make it impossible to deal with questions related to ethics; in the second chapter we will make a relation between logic and ethics, clarifying what reality and the world are in an attempt to understand how Wittgenstein proposes to speak about 'saying' and 'showing'; in the third chapter we make an approach about the will, considered as attribute of the subject, and finally are made the clarifications necessary to know the ethics defended by the author. At this point the research brings to light the difference put by Wittgenstein concerning the subject, which in turn is divided into empirical and metaphysical. All discussions culminate in the idea that there is an ethical content in the Tractatus that leads the subject to understand the world in its totality and while he reaches this understanding he has the possibility of finding happiness knowing the real meaning of life.